2018
DOI: 10.1007/s12022-018-9514-y
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 and IDO1 Are Expressed in Poorly Differentiated Thyroid Carcinoma

Abstract: Poorly differentiated thyroid carcinoma (PDTC) is an aggressive form of thyroid cancer that currently has limited effective treatment options. Immune checkpoint inhibitors (ICIs) have shown to be an effective treatment for a variety of carcinomas. In this study, we explore whether immune checkpoint pathways, such as programmed cell death ligand 1 (PD-L1) and indoleamine 2,3-dioxygenase 1 (IDO1), are activated in a cohort of patients with PDTC to determine whether ICIs may be an effective therapy for these pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 63 publications
3
44
0
1
Order By: Relevance
“…In recent years, a few studies investigating PD‐L1 in thyroid cancer have established a frequency of expression ranging between 23% and 87% in thyroid carcinoma . Interestingly, some studies reported diffuse and strong PD‐L1 expression in anaplastic thyroid carcinoma . Anti–PD‐L1 immunotherapy may offer a novel means for managing unresponsive patients afflicted by this particularly aggressive thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a few studies investigating PD‐L1 in thyroid cancer have established a frequency of expression ranging between 23% and 87% in thyroid carcinoma . Interestingly, some studies reported diffuse and strong PD‐L1 expression in anaplastic thyroid carcinoma . Anti–PD‐L1 immunotherapy may offer a novel means for managing unresponsive patients afflicted by this particularly aggressive thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis by Aghajani et al, which included 721 patients with nonmedullary thyroid carcinomas, showed a significant association between PD‐L1 positivity, tumor recurrence, and poor survival, suggesting a possible role of PD‐L1 as a prognostic marker (akin to BRAF V600E). Conversely, although PD‐L1 in PDTC was significantly associated with tumor size and multifocality, there was only a nonsignificant trend toward an association with prognostic factors . Thus, prospective clinical trials are needed to support these findings for different thyroid cancers.…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 96%
“…Cunha et al analyzed 293 PTCs/follicular thyroid carcinomas, 114 benign nodules, and 5 normal tissues and concluded that PD‐L1 (B7‐H1) immunohistochemistry did not have diagnostic utility . The study by Rosenbaum et al on poorly differentiated thyroid carcinoma (PDTC) also supports the concept that PD‐L1 staining is often limited, focal, and heterogeneous, limiting its use as a diagnostic marker . Fu et al analyzed the expression of PD‐L1 in 52 NIFTPs, 45 invasive encapsulated follicular variants of PTC (EFVPTCs), and 40 benign nodules .…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 99%
See 2 more Smart Citations